Current status and trends of leather production in Türkiye - Kılınç, Kemal (İdris Karagöz, 2026)
The leather production sector is based on processing raw hides and skins, which are by-products of the meat and dairy industries, into usable materials. Türkiye stands out as one of the world's leading countries in this field, thanks to its rich leather processing heritage and production capacity. In this study, the leather production industry, which is also called the ‘tanning industry’ apart from the leather products industry, is analysed in terms of raw materials, production facilities and processes, regions where leather is produced, Türkiye's foreign trade in the leather production sector and trends in leather production, based on the presence and slaughter numbers of cattle, sheep and goats, which are raw material sources in Türkiye. Türkiye is one of the 10 largest leather producers in the world in terms of production volume, it is a country that carries out most of its leather production with imported raw hides and skins due to insufficient local raw hide and skins resources, leather production is concentrated in certain organised industrial zones, and in foreign trade, it is a country with high import rates against a significant amount of exports. Among the trends in leather production in Türkiye, export orientation, increasing production quality standards, tendency to do business together, innovative approaches in marketing strategies, contract manufacturing and close relations with the food industry stand out. With this study, which aims to contribute to the literature by evaluating the current situation and future perspectives of the leather production industry in Türkiye, the capacity of the leather production sector in Türkiye to maintain its strength in global markets can be clearly seen.

Deri üretim sektörü, et ve süt endüstrisinin yan ürünü olan ham derilerin işlenerek kullanılabilir hale getirilmesine dayanır. Türkiye, bu alanda sahip olduğu zengin deri işleme mirası ve üretim kapasitesiyle dünyada öne çıkan ülkelerden biridir. Bu çalışmada, deri mamulleri sektöründen ayrı olarak “tabaklama sektörü” de denilen deri üretim endüstrisi; Türkiye özelinde hammadde kaynağı olan sığır, koyun ve keçi varlığı ve kesim sayıları da esas alınarak; ham deri, üretim tesisleri ve prosesleri, deri üretiminin yapıldığı bölgeler, deri üretim sektöründe Türkiye’nin dış ticareti ve deri üretimindeki trendler açısından incelenmiştir. Türkiye deri üretiminde, hacimsel olarak dünyadaki en büyük 10 deri üreticisi arasında bulunan, yerel ham deri kaynakları yetersiz kaldığı için deri üretiminin büyük kısmını ithal ham derilerle yürüten, deri üretiminin belirli organize sanayi bölgelerinde yoğunlaştığı, dış ticarette ise önemli miktarda ihracata karşı ithalat oranları da yüksek olan bir ülke konumundadır. Türkiye’de deri üretimindeki trendler arasında ihracata yönelme, üretim kalite standartlarının artırılması, birlikte iş yapma eğilimi, pazarlama stratejilerinde yenilikçi yaklaşımlar, fason üretim ve gıda sanayisi ile yakın ilişkiler gibi unsurlar öne çıkmaktadır. Türkiye'deki deri üretim endüstrisinin mevcut durumunu ve gelecek perspektiflerini değerlendirerek literatüre katkı sağlamayı amaçlayan bu çalışma ile Türkiye’deki deri üretim sektörünün küresel pazarlarda gücünü koruma kapasitesi açıkça görülebilmektedir.
Türkiye’de deri üretiminin mevcut durumu ve trendleri
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri [EN] Leather Engineering; Deri Mühendisliği